The leadership of The Head of Madrasah in Improving Quality of Education - Uka Sugiri; Sya’roni Ma’shum (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
This article aims to analyze the strategies of madrasah principals used in improving the quality of education and to describe the type or character of madrasah principals' leadership in improving the quality of education. The method in this research is descriptive-qualitative. The selection of this method will make it easier to understand the data exposure that has been explained because it is arranged accurately and systematically. The data collection of this research used the methods of observation, interviews, and documentation. After that the data that has been collected is analyzed in the stages of data reduction, data presentation and the last is drawing conclusions. The results that can be presented in this study are several strategies used by the madrasa principal to achieve a target that has been jointly set by all school components. The strategy adopted by the madrasah principal certainly refers to the exposure of the theory about the quality of an education which includes existing inputs, processes, and outputs. From the implementation of this strategy, it can also be seen how the character or type of leadership of the madrasah principal, which, according to several data sources, leads to democratic leadership. This can be seen from the thought intervention of related parties in issuing a school policy.